Software for productivity calculation of polypropylene filtering element in dependence from its application - Vecherkovskaya, Anastasia; Popereshnyak, Svitlana (Technology audit and production reserves, 2017)
The object of research is the process of FVNM manufacturing. One of the most problematic places in the production of filter materials is the lack of recommendations for determining the structure of these elements, depending on the field of application. In the course of research, the main application areas of the elements, which are made of «foamed» polypropylene, were analyzed. As a result of the analysis it is revealed that the main functions that these elements perform are mainly drainage or filtering. A one-component model of suspension flow through a porous medium is considered, granulometric analysis of the purified liquid is carried out and the percentage state of the filtrate is obtained depending on the particle size. This result allows to see that the distribution of the filtrate as a function of time can be divided into groups: almost 30 % – 1–5 μm; almost 60 % – 10–50 μm. It is found that, depending on the field of application and the purpose of the filter element, it can have a different number of layers and a different structure of these layers. Using the results of granulometric analysis, it can be concluded that 70 % of the filter elements have a three-layer structure. The construction of a multilayer filter element by changing the air pressure on the equipment to form FVNM is experimentally proved. The technique for organization of calculations of the amount of filtering material of a certain structure is obtained depending on: – filtration process that involves determining the input data of a liquid or gas that will be filtered; – formulas for calculating the luminous efficiency of the filter and the filtration performance. This technique is practical in nature and can be applied in production. This technique has improved the interaction with customers by 40 %, due to a faster calculation of the required amount of filter material and the formation of the final cost of the order. Thanks to the obtained calculations, a prototype of a software tool has been developed that allows selecting the structure and dimensions of the filter element depending on the application and media. After the testing phase, this software will be used as one of the modules of the process automation system for production of polypropylene mechanical cartridges with subsequent introduction at the enterprises that manufacture filter elements.